Psychological capital and perceived supervisor social support as mediating roles between role stress and work engagement among Chinese clinical nursing teachers: a cross-sectional study - Haiyan Yin; Xiangjie Sun; Chunlan Liu; Fenge Zhao (BMJ Open)
Objective This study aimed to investigate the work engagement of clinical nursing teachers and examine whether psychological capital and perceived supervisor social support mediates the association between role stress and work engagement among clinical nursing teachers.Design A cross-sectional study design was used.Setting This study was conducted in five tertiary hospitals affiliated with medical universities in Shandong Province, China.Participants A total of 412 clinical nursing teachers were recruited out of which 406 completed the questionnaires effectively.Methods Questionnaires were administered offline and the items consisted of social demographic characteristics, scale related to role stress, psychological capital, perceived supervisor social support and work engagement. T-tests, one-way analysis of variance and Pearson’s correlation analysis were conducted using SPSS, and mediation analysis was performed using structural equation modelling.Results The work engagement scores of clinical nursing teachers were high, with an average score of 4.76±0.69. Structural equation modelling showed a good fit of the data to the hypothesised model. Role stress did not directly affect work engagement (β=0.057, p>0.001). However, a strong indirect effect of role stress on work engagement (β=−0.373, p<0.001) mediated by psychological capital and perceived supervisor social support was observed, with path coefficient of −0.319 (p<0.01) and −0.054 (p<0.01), respectively. The model explains 57% of the variance in work engagement.Conclusion Psychological capital and perceived supervisor social support fully mediated the relationship between role stress and work engagement among clinical nursing teachers. Thus, to promote the work engagement of clinical nursing teachers, their psychological capital needs to be improved. Furthermore, superiors should provide more support, particularly to clinical nursing teachers experiencing high role stress.